Pola Alih Tutur dalam Webseries berjudul ‘SORE-Istri dari Masa Depan’ - Abiyan Fitri Maulana; Mohamad Syahril Rhomadon; Merlina Guspita (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study examines the patterns of speech transfer in the YouTube series